Efektivitas Proyek Penguatan Profil Pelajar Pancasila (P5) dalam Meningkatkan Kreativitas pada Anak Usia 4-5 Tahun di TK Dharma Wanita Kadidi Kabupaten Sidrap - Asni, Asni; Natsir, Tri Ayu Lestari; Ashari, Novita; Palintan, A. Tien Asmara (LP. Ma'arif Janggan Magetan, 2024)
This study was motivated by the low creativity of children aged 4-5 years at Dharma Wanita Kadidi Kindergarten, Sidrap Regency. The purpose of this study was to determine the effect of the effectiveness of the Pancasila Student Profile Strengthening Project (P5) in increasing creativity in children aged 4-5 years at Dharma Wanita Kadidi Kindergarten, Sidrap Regency. This study used a pre-experimental design method with a one group pretest-posttest type. The population used was children aged 4-5 years at Dharma Wanita Kadidi Kindergarten, Sidrap Regency, consisting of 7 boys and 7 girls. Data collection techniques were in the form of tests and documentation. The data analysis technique used was using the SPSS version 22 program. The results of this study concluded that from the level of children's creativity abilities before being given treatment (pretest) with the final mean result of 5.64 out of 14 children while the final mean result after being given treatment (posttest) was 12. 43 out of 14 children. The results of the hypothesis test (t-test) obtained a significance value (sig.) of 0.000, it can be said that 0.000 <0.05. So it can be concluded that Ha is accepted and Ho is rejected, which means that there is an influence of the effectiveness of the Pancasila Student Profile Strengthening Project (P5) in increasing the creativity of children aged 4-5 years at Dharma Wanita Kadidi Kindergarten, Sidrap Regency.